Influence of tool offsetting and base metal positioning on the material flow of AA5052-AA6061 dissimilar friction stir welding - L. H., Shah; Midawi, Abdelbaset R. H.; Walbridge, Scott; Gerlich, Adrian (Faculty Mechanical Engineering, UMP, 2020)
This study examines dissimilar friction stir welding of AA5052-AA6061 aluminum alloys with varying tool offsets. The base metals were positioned and fixed at a slight diagonal positioning such that varying tool offset position from the centreline can also be varied along the length of the weld. After the fabrication process, microstructural and mechanical property characterization was subsequently conducted. The results show that, above a certain threshold for to ol offset, incomplete consolidation (i.e. kissing bond efects) will occur. Regardless of the base material positioning, a zero tool offset shows optimum intermixing in the stir zone. EDX mapping confirms the presence of a distinct interface between both materials in the stir zone region. However, enhanced material intermixing and better elongation are observed when AA6061 alloy is positioned at the tool advancing side.